QUANTITATIVE AND QUALITATIVE EXAMINATION OF ANTHROPOMETRICAL PARAMETERS IN PRESCHOOL CHILDREN WITH SELF-ORGANIZING MAPS - Trpkovska, Biljana; Zafirova, Biljana; Chadikovska, Elizabeta; Stojanoska, Biljana Bojadzieva (Journal of Morphological Sciences; Vol 3 No 1 (2020): JMS, 2020)
Growth monitoring and promotion of optional growth are essential components of primary health care for children. Serial measurements of weight, height/length, for all children and measurements of circular and transversal parameters compared with growth of large sample population help to confirm a child's healthy growth and development. It also allows early identification of potential nutritional or health problems and enables prompt action before a child's health is seriously compromised. The aim of the study was to compare quantitative and qualitative examination of anthropometric parameters as indicator of growth and nutritional status in preschool children. Anthropometric parameters were measured on healthy children, defining longitudinal, circular and transversal dimensionality of the skeleton using standard technique and instruments. The qualitative examination was detected with self- organizing maps. The majority of anthropometrical parameters have shown significant age and sex specific differences in favour of female subjects. The height-for-age index values corresponding to the 50 th percentile showed slightly higher values in our female subjects 115.4 cm than in our male subjects 113.2 cm. The values of 50 th percentile of BMI in our male subjects were 15.94 kg/m Â², whereas in our females were 15.64 kg/mÂ². These results show that obesity prevention is recommended, and detected values could be applied for evaluation of deviations in growth and nutritional status in preschool children. Key words: anthropometry, growth, self-organizing maps,preschool children.